Impact of Lipid Peroxidation on the Physiology and Pathophysiology of Cell Membranes - Angel Catala (Frontiers Research Topics, 2017)
The general process of lipid peroxidation consists of three stages: initiation, propagation, and termination. The initiation phase of lipid peroxidation includes hydrogen atom abstraction. Several species can abstract the first hydrogen atom and include the radicals: hydroxyl, alkoxyl, peroxyl, and possibly HO* 2. The membrane lipids, mainly phospholipids, containing polyunsaturated fatty acids are predominantly susceptible to peroxidation because abstraction from a methylene group of a hydrogen atom, which contains only one electron, leaves at the back an unpaired electron on the carbon. The initial reaction of *OH with polyunsaturated fatty acids produces a lipid radical (L*), which in turn reacts with molecular oxygen to form a lipid hydroperoxide (LOOH). Further, the LOOH formed can suffer reductive cleavage by reduced metals, such as Fe++, producing lipid alkoxyl radical (LO*). Peroxidation of lipids can disturb the assembly of the membrane, causing changes in fluidity and permeability, alterations of ion transport and inhibition of metabolic processes. In addition, LOOH can break down, frequently in the presence of reduced metals or ascorbate, to reactive aldehyde products, including malondialdehyde (MDA), 4-hydroxy-2-nonenal (HNE), 4-hydroxy-2-hexenal (4-HHE) and acrolein. Lipid peroxidation is one of the major outcomes of free radical-mediated injury to tissue mainly because it can greatly alter the physicochemical properties of membrane lipid bilayers, resulting in severe cellular dysfunction. In addition, a variety of lipid by-products are produced as a consequence of lipid peroxidation, some of which can exert beneficial biological effects under normal physiological conditions. Intensive research performed over the last decades have also revealed that by-products of lipid peroxidation are also involved in cellular signalling and transduction pathways under physiological conditions, and regulate a variety of cellular functions, including normal aging. In the present collection of articles, both aspects (adverse and benefitial) of lipid peroxidation are illustrated in different biological paradigms. We expect this eBook may encourage readers to expand the current knowledge on the complexity of physiological and pathophysiological roles of lipid peroxidation.